Two new Pythium species from southern China based on morphological and molecular characters - Chen, Jia-Jia; Feng, Hui; Song, Wei; Zheng, Xiao-Bo (Phytotaxa, 2020)
Two new species of Pythium, namely P. subinflatum and P. xuzhouense, from soybean (Glycine max) in southern China are described based on their morphology and molecular phylogenetic analyses inferred from the internal transcribed spacer region of the ribosomal RNA gene and mitochondrial cytochrome c oxidase subunit I gene. Pythium subinflatum is characterized by globose to sub-globose or ovoid hyphal swellings, filamentous inflated sporangia, smooth oogonia, mostly diclinous antheridia, elongated along the oogonial stalk, subcircular, subglobose or fist-shaped antheridial cells, and aplerotic and slightly thick-walled oospores (2–3.5 µm); P. xuzhouense differs from other species in the genus by filamentous or lobulated sporangia, smooth oogonia, mostly diclinous, sometimes monoclinous antheridia, subclavate, falcate or semicircle to subcircular antheridial cells, and plerotic or nearly plerotic and thin-walled oospores (0.5–1.5 µm). In addition, the two new species are compared to closely related Pythium species regarding their phylogenetic positions and morphological features.